2010
DOI: 10.1093/molehr/gaq057
|View full text |Cite
|
Sign up to set email alerts
|

Genes for prostaglandin synthesis, transport and inactivation are differentially expressed in human uterine tissues, and the prostaglandin F synthase AKR1B1 is induced in myometrial cells by inflammatory cytokines

Abstract: Prostaglandins (PGs) are important factors in the physiology of human parturition and the control of uterine contractility. We have characterized the expression of 15 genes from all stages of the PG pathway in human pregnant and non-pregnant (NP) myometrium and in other uterine tissues at delivery, and the results show patterns indicative of different capacities for PG synthesis and catabolism in each tissue. In placenta, the PG synthase expression profile favours production of PGD₂, PGE₂ and PGF₂, with high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 61 publications
2
24
1
Order By: Relevance
“…These results suggest that the NMB elicit increased [Ca 2þ ] i depending on the joint presence of extracellular calcium via PKC, and it may involve other pathways in Nmbr-mediated effects on myometrial cell activity. Related studies have shown that Nmbr activation stimulates phospholipase A2 and phospholipase D via both PKC-dependent and independent mechanisms [29]. Phospholipase A2 activity is a crucial enzyme in the regulation of the production and release of prostaglandin, which induces myometrium contraction and cervix ripening [29,30].…”
Section: Zhang Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that the NMB elicit increased [Ca 2þ ] i depending on the joint presence of extracellular calcium via PKC, and it may involve other pathways in Nmbr-mediated effects on myometrial cell activity. Related studies have shown that Nmbr activation stimulates phospholipase A2 and phospholipase D via both PKC-dependent and independent mechanisms [29]. Phospholipase A2 activity is a crucial enzyme in the regulation of the production and release of prostaglandin, which induces myometrium contraction and cervix ripening [29,30].…”
Section: Zhang Et Almentioning
confidence: 99%
“…Related studies have shown that Nmbr activation stimulates phospholipase A2 and phospholipase D via both PKC-dependent and independent mechanisms [29]. Phospholipase A2 activity is a crucial enzyme in the regulation of the production and release of prostaglandin, which induces myometrium contraction and cervix ripening [29,30]. Moreover, Nmbr stimulation also results in activation of tyrosine kinases and tyrosine phosphorylation of p125FAK by a phospholipase C-independent mechanism which requires p21 and the integrity of the actin cytoskeleton [31].…”
Section: Zhang Et Almentioning
confidence: 99%
“…We previously compared the relative levels of expression of 15 genes acting in all stages of prostaglandin metabolism (their relationships are illustrated in Figure 1) in human uterine tissues [13], demonstrating specific capacities for synthesis and catabolism of PGD 2 , PGE 2 , PGF 2 and PGI 2 in each tissue. We have now made a detailed examination of these genes in samples of placenta, choriodecidua and amnion, demonstrating that factors such as gestational age and the incidence and duration of labour are associated with significant changes in expression patterns.…”
Section: Introductionmentioning
confidence: 99%
“…During labour there is increased synthesis of prostaglandins (PGs) within the uterus via the induction of prostaglandin-endoperoxide synthase (PTGS), also known as cyclooxygenase (COX) [8]. COX is a rate limiting enzyme that is responsible for the conversion of arachidonic acid to prostaglandin endoperoxides, which are further converted into different prostaglandins (PGs) by cell specific terminal synthases [9-11]. Besides relaxation and contraction of the myometrium, PGs also stimulate cervical ripening.…”
Section: Introductionmentioning
confidence: 99%
“…epidermal growth factor (EGF)), phorbol esters (e.g. phorbol-12-myristate-13-acetate (PMA)) and by the potent uterotonic hormone oxytocin (OXT) [9,13-16]. …”
Section: Introductionmentioning
confidence: 99%